1983
DOI: 10.1068/p120549
|View full text |Cite
|
Sign up to set email alerts
|

Visual Apparent Movement: Transformations of Size and Orientation

Abstract: Sequential alternation between same-shaped stimuli differing in size (size ratio s) and orientation (angular difference v) produced a visual illusion of translation in depth and concurrent rotation. The minimum stimulus-onset asynchrony required for the appearance of a rigidly moving object was approximately a linearly increasing function of (s-1)/(s+1) for simple translation in depth and a linearly increasing function of v for simple rotation. The extrapolated zero intercept was lower for translation than for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
81
0
1

Year Published

1983
1983
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(95 citation statements)
references
References 27 publications
13
81
0
1
Order By: Relevance
“…2 The results of Bundesen et al (1981) confirmed the prediction of additivity for rotations in the picture plane, and also for combinations of rotations and size scalings, providing evidence for analogue rotation and scaling processes in object recognition. The importance of these findings is increased by the fact that sequential additivity for rotations could be demonstrated even though the RT function was nonlinear.…”
Section: Analogue Transformation Processes In Mental Imagery and In Omentioning
confidence: 56%
See 1 more Smart Citation
“…2 The results of Bundesen et al (1981) confirmed the prediction of additivity for rotations in the picture plane, and also for combinations of rotations and size scalings, providing evidence for analogue rotation and scaling processes in object recognition. The importance of these findings is increased by the fact that sequential additivity for rotations could be demonstrated even though the RT function was nonlinear.…”
Section: Analogue Transformation Processes In Mental Imagery and In Omentioning
confidence: 56%
“…According to TFR, both mental imagery and object recognition rely on time-consuming and error-prone transformation processes in order to achieve an alignment of two representations, which results in a systematic dependency of performance on the amount of transformation. In addition, transformation processes in imagery and recognition seem to be analogue processes (Bundesen et al, 1981;Cooper, 1976;Kourtzi & Shiffrar, 2001). …”
Section: The Relation Between Object Recognition and Mental Rotationmentioning
confidence: 99%
“…In 1991, a new type of motion illusion was discovered that seemed difficult to explain using standard models of motion processing (Hikosaka, Miyauchi,& Shimojo, 1991, 1993a, 1993b; for partial precedents, however, see Bundesen, Larsen, & Farrell, 1983, Farrell & Shepard, 1981, Hartmann, 1923, Kanizsa, 1951, Kenkel, 1913, Kolers & Pomerantz, 1971, Orlansky, 1940, and Shepard, 1984. Several investigators examined simple two image motion sequences in which one shape was replaced all at once by another one that overlapped the first.…”
Section: The Duration Of 3-d Form Analysis In Transformational Apparementioning
confidence: 99%
“…The observer in these cases sees an object changing color midway between the endpoints of its trajectory, or a smoothly changing shape. This filling-in process is known as impletion (see,e.g., Bundesen, Larsen, & Farrell, 1983;Farrell & Shepard, 1981; chapter 6 of Kanizsa, 1979;Orlansky, 1940;Shepard, 1984). One can argue that impletion reflects an implicit inference made by the visual system, which interprets ambiguous stimuli in terms of the most likely real-world state of affairs.…”
Section: Princeton Universitymentioning
confidence: 99%